Targeting stemness pathways modulates macrophage polarization and reprograms the tumor microenvironment - Butkute, Austeja; Baltramonaitis, Marius; Malmige, Simona; Darinskas, Adas; Pasukoniene, Vita; Mlynska, Agata (Frontiers in Immunology, 2025)
IntroductionThe tumor microenvironment plays a pivotal role in cancer progression and therapeutic resistance, with tumor-associated macrophages significantly influencing immune suppression and tumor growth. Colorectal cancers (CRC) classified as Consensus Molecular Subtype 4 (CMS4) and triple-negative breast cancers subsets are particularly characterized by a mesenchymal phenotype, immune exclusion, and extensive macrophage infiltration. This study aimed to investigate how targeting cancer cell stemness with specific inhibitors could modulate macrophage polarization in CRC in vitro and breast cancer in vivo, potentially shifting the immune balance from pro-tumor M2-like to anti-tumor M1-like macrophages. MethodsWe used four stemness inhibitors—salinomycin, SB-431542, JIB-04, and napabucasin—each targeting different pathways (Wnt/β-catenin, TGF-β, histone demethylation, and STAT3, respectively), to evaluate their effects on CMS4 CRC cell lines (HCT116 and SW620) and human peripheral blood-derived macrophages in an indirect co-culture model. ResultsOur results showed that CMS4 CRC cell lines induced distinct macrophage polarization patterns, with HCT116 promoting M2-like macrophages and SW620 leaning toward M1-like profile. Notably, the combination of stemness inhibitors reduced stemness markers (CD133, CD44) in colorectal cancer cells and shifted macrophage polarization toward an M1-like phenotype, particularly in co-culture with HCT116. In vivo studies using the syngeneic immunocompetent EO771 breast cancer mouse model demonstrated that combination of stemness inhibitors increased the M1/M2 macrophage ratio.ConclusionsOur study highlights the dual potential of stemness inhibitors to target both cancer cells and the immune microenvironment. These findings offer promising strategies for enhancing favorable immunomodulation in mesenchymal-like colorectal tumors.